The mechanism and kinetics of void formation and growth in particulate filled PE composites (eXPRESS Polymer Letters)
Volume strain measurements were carried out on PE/CaCO3 composites prepared with three different matrix polymers, containing various amounts of filler. The analysis of the debonding process and the various stages of void formation proved that the model developed for the prediction of the initiation of debonding is valid also for the studied PE/CaCO3 composites. Debonding stress is determined by the strength of interfacial adhesion, particle size and the stiffness of the matrix. In thermoplastic matrices usually two competitive processes take place: debonding and the plastic deformation of the polymer. The relative magnitude of the two processes strongly influences the number and size of the voids formed. Because of this competition and due to the wide particle size distribution of commercial fillers, only a certain fraction of the particles initiate the formation of voids. The number of voids formed is inversely proportional to the stiffness of the matrix polymer. In stiff matrices almost the entire amount of filler separates from the matrix under the effect of external load, while less than 30% debond in a PE which has an initial modulus of 0.4 GPa. Further decrease of matrix stiffness may lead to the complete absence of debonding and the composite would deform exclusively by shear yielding. Voids initiated by debonding grow during the further deformation of the composite. The size of the voids also depends on the modulus of the matrix. The rate of volume increase considerably exceeds the value predicted for cross-linked rubbers. At the same deformation and filler content the number of voids is smaller and their size is larger in soft matrices than in polymers with larger inherent modulus.